Peningkatan Pengetahuan Petani Jagung Pakpak Bharat dalam Mengolah Limbah Pangkal Jagung Menjadi Pupuk Organik Ramah Lingkungan - Sari, Sri Adelila; Prastowo, Puji; Muslim; Kabeakan, Feri Yuni; Hasibuan, Hanisah; Nasution, Lia Mardiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Pakpak Bharat Regency in North Sumatra Province has significant potential in the agriculture sector, particularly in corn cultivation. However, the management of corn waste in this region has been suboptimal, with corn cobs often left to accumulate or burned, leading to environmental pollution. Limited technology and the high cost of equipment have hindered the community from processing this waste into organic fertilizer, resulting in dependence on externally purchased organic fertilizers. This study was aimed to enhance corn farmers' knowledge about processing corn cob waste into organic fertilizer. The methods used were included education, provision of appropriate technology (TTG) in the form of shredders, and training and mentoring in organic fertilizer production. Data were analyzed using scoring methods and Spearman Rank. The results were indicated a significant increase in corn farmers' knowledge in Pakpak Bharat regarding the processing of corn cob waste into organic fertilizer, with scores were rised from 1.57 (low) to 2.80 (high). Factors contributing to this improvement were included of age (rs=0.410*), education (rs=0.500*), and technology suitability (rs=0.620*). Through this activity, farmers learned to convert corn cob waste into organic fertilizer, which reduced environmental impact and improved their income and quality of life. Abstrak Kabupaten Pakpak Bharat, Provinsi Sumatera Utara, memiliki potensi besar dalam sektor pertanian, khususnya dalam budidaya jagung. Namun, pengelolaan limbah jagung di wilayah ini masih belum optimal, dengan limbah pangkal jagung sering dibiarkan menumpuk atau dibakar, mengakibatkan pencemaran lingkungan. Keterbatasan teknologi dan biaya pengadaan alat yang mahal menghambat masyarakat dalam mengolah limbah ini menjadi pupuk organik, serta ketergantungan pada pupuk organik yang dibeli dari luar. Penelitian ini bertujuan untuk meningkatkan pengetahuan petani jagung tentang pengolahan limbah pangkal jagung menjadi pupuk organik. Metode yang digunakan mencakup edukasi, penyediaan teknologi tepat guna (TTG) berupa alat pencacah, serta pelatihan dan pendampingan dalam produksi pupuk organik. Data dianalisis menggunakan metode scoring dan Rank Spearman. Hasil penelitian menunjukkan peningkatan signifikan dalam pengetahuan petani jagung di Pakpak Bharat mengenai pengolahan pupuk organik dari limbah pangkal jagung, dari skor 1,57 (rendah) menjadi 2,80 (tinggi). Faktor-faktor yang berkontribusi terhadap peningkatan ini meliputi umur (rs=0,410*), pendidikan (rs=0,500*), dan kesesuaian teknologi (rs=0,620*). Melalui kegiatan ini, para petani jagung memperoleh pengetahuan dalam mengolah limbah tongkol jagung menjadi pupuk organik, yang tidak hanya mengurangi dampak lingkungan dari pembakaran limbah tetapi juga pendapatan dan kualitas hidup mereka mestinya dapat ditingkatkan.